Flaxseed oil weight loss supplement in women: quasi-experimental study - Bora, Yohana; Titisari, Ira; Kundarti, Finta Isti; Rahmawati, Rahajeng Siti Nur (Universitas Aisyiyah Yogyakarta, 2024)
The prevalence of obesity and overweight in 2018 was more than 650 million people. Treatment of obesity includes both non-pharmacological and pharmacological approaches, including the use of flaxseed oil. flaxseed oil, containing about 40% oil with ALA as the main component, provides omega-3 fatty acids that reduce inflammation associated with obesity, and its high soluble and insoluble fiber content increases satiety, reduces calorie intake, and improves digestive health. This study aimed to find out how flaxseed oil supplements affect body weight in women. This study used a quasi-experimental design with a control group that included a pre and post-test. Respondents used amounted to 78 people who were divided into 2 groups, namely intervention (39 participants) and control (39 participants) in the working area of Puskesmas Pesantren II and Puskesmas Kota North Region of Kediri City. The sampling technique used simple random sampling. The intervention group was given standard care and flaxseed oil supplement 1 x 1000 mg daily for 12 weeks, while the control group only received standard care. With a p-value of 0.460, the Wilcoxon test on the experimental group for body weight revealed statistically insignificant findings. In contrast, a p-value of 0.356, was observed for body weight in the control group. On the post-test difference in body weight, the p-value was 0.024. flaxseed oil supplementation reduces body weight in women. This study is expected to help health workers to provide flaxseed oil supplements to obese women as an alternative treatment.